Al-TiH2 Composite Foams Magnesium Alloy - A. K., Prasada Rao; Oh, Y. S.; Ain, W. Q.; Azhari, A.; Basri, S.; Kim, N. J. (IOP Publishing, 2016)
The work presented here in describes the synthesis of aluminum based titanium-hydride particulate composite by casting method and its foaming behavior of magnesium alloy. Results obtained indicate that the Al-10TiH2 composite can be synthesized successfully by casting method. Further, results also reveal that closed-cell magnesium alloy foam can be synthesized by using Al-10TiH2 composite as a foaming agent.